(untitled) (Traffic Safety Research, 2024)
Stakeholders in many municipalities worldwide are committed to promoting cycling and improving cycling provision. Scarcity of space is a major issue in most of these cities, particularly for main streets with significant movement and place functions. Multiple demands exist on these streets, including moving pedestrians, cyclists, motorised vehicles, parking, people waiting at public transport stops, or staying in the street for place activities. Mixing cyclists and motorised vehicles in the same space in the carriageway might be the only possible solution for cycling provision in these contexts, which is applied in many German cities. The aim of this study is to evaluate the acceptance of cycling in mixed traffic, which we measure as the proportion of cyclists riding on the carriageway versus on the pavement. The empirical work in this study is based on video observations at 273 study sites with a total length of 124 km located in 13 cities in Germany. 260 of these study sites have no marking for cyclists, and 13 have bicycle pictograms. A total of 34 874 cyclists are recorded at these study sites. A logistic regression model is used to quantify the effect of exposure and infrastructure characteristics on the proportion of cyclists on the carriageway. Volumes of motorised vehicles, lane widths > 3.00 m and city type show a significant negative effect on the acceptance of cycling on the carriageway. Cyclist volumes, bicycle pictograms, and a speed limit < 50 km/h significantly increase the likelihood of cycling on the carriageway. The model is then applied to develop evidence-based recommendations on appropriate conditions for mixed traffic provision for cyclists, ensuring pre-defined levels of acceptability. Cycling in mixed traffic without bicycle pictograms should only be recommended with traffic volumes of a maximum of 400 vehicles per hour and a speed limit of < 50 km/h to achieve a proportion of cyclists on the carriageway of 90%. The marking of bicycle pictograms increases acceptance.